Internalization of Religious Values through Tadzkiroh and Khotmul Qur'an Programs to Reduce Sarcasm Behavior in Generation-Z (Case Study at SMA Informatika Serang City) - Murniasih, Eri; Abdul Mujib; Hunainah (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2024)
Sarcasm behavior is one of the social phenomena among Generation Z. Sarcasm, which is often used as a form of joking humor or criticism, can have a negative impact on interpersonal communication and individual mental health. This study aims to examine how the Tadzkiroh & Khotmul Qur'an program internalizes religious values in order to reduce sarcasm among Generation Z. This research uses a qualitative descriptive approach method with the type of case study conducted at SMA Informatika Serang City. Data were collected through in-depth interviews and program observations. The results showed that the internalization of religious values such as responsibility, honesty, empathy, and mutual respect and compassion in the Tadzkiroh & Khotmul Qur'an program includes three stages; value transformation, value transaction and value internalization which contribute to the prevention of sarcasm behavior among students. This article recommends the widespread implementation of similar programs in various educational institutions as a preventive effort against negative behavior and as a means of forming a noble young generation.